Chemical constituents from the Dendrobium officinale and their chemotaxonomic significance. (June 2022) - Xu, Xue-Feng; Dai, De-Cai; Yan, Hao; Zhang, Yu
Abstract: The phytochemical investigation of the stems of Dendrobium officinale Kimura et Migo led to the isolation of a new chromone, chromcinale (1 ) and a new phenolic glycoside, leonuriside C (5 ), together with three known biogenetically related phenanthrenes (2 –4 ), three known biogenetically related phenolic glycosides (6 –8 ) and four known biogenetically related phenylpropanoids (9 –12 ). The structures of these compounds were elucidated using comprehensive spectroscopic methods. Compounds 1–3, 5–12 were isolated from the D. officinale for the first time. The chemotaxonomic significance of the isolates was also discussed. Graphical abstract: Image 1 Highlights: A new chromone, chromcinale and a new phenolic glycoside, leonuriside C from the Dendrobium officinale . Compounds 1–3, 5–12 were isolated from the Dendrobium officinale for the first time. Compounds 1 -12 may have a role as chemotaxonomic markers for Dendrobium officinale.